MSME Strategy In Marketing Products In The Pandemi Of Covid-19 In The New Normal Era - Muh. Fahrurrozi; Mispandi Mispandi (Universitas Hamzanwadi, 2023)
This study aims to examine the product marketing strategies implemented by Micro, Small and Medium Enterprises (MSMEs) during the COVID-19 pandemic. The object of research is SMEs in East Lombok. The method used is a qualitative research method with a descriptive approach. Based on the results of the study obtained data that the business strategy in marketing its products is through social media, promotions, and giving discounts. The results of the study illustrate that the marketing strategy used by MSME actors in East Lombok can work by paying attention to consumer purchasing power during the COVID-19 pandemic. By using social media facilities, the funds needed by small business actors have an impact on increasing MSME income. The role of the government and banks is very important, especially related to training in the use of information technology so that small business products can survive in the midst of the COVID-19 pandemic